PTU-254 Incidence, presentation and outcomes for patients with ischaemic colitis admitted to an open-access gi bleeding unit. (22nd June 2015) - Reilly, A; Leeds, J; Phull, P
Abstract : Introduction: Ischaemic colitis (IC) is the most common form of gastrointestinal ischaemia; an acute impairment of perfusion of the colon leads to mucosal injury resulting in inflammation, ulceration and occasionally full-thickness necrosis. A recent meta-analysis has suggested that ∼20% of patients require surgery, and the mortality rate is almost 13%. 1 The aim of this study was to determine the incidence, presentation and outcomes for patients with ischaemic colitis. Method: Retrospective audit of prospectively collected data for the open-access GI Bleeding Unit (GIBU) at our institution between January 1995 and December 2004. Data was extracted from the GIBU database for all patients coded as IC or 'other colonic' diagnoses. The diagnosis of IC was validated by cross-checking with the hospital endoscopy and pathology software systems. Results: Over the 10 year period studied, there were 1885 admissions with lower GI bleeding of which 108 (5.7%) had an endoscopically and/or histologically confirmed diagnosis of IC. The number of cases of IC increased over time; the incidence of bleeding from ischaemic colitis increased from 0.24 per 100, 000 in 1995 to 5.06 per 100, 000 of the adult population in 2004. The mean age of the patients was 69 (range 35–91) years, with 93 (86.1%) being >55 yrs; 83 (76.9%) were female. Presentation was with rectal bleeding in 103 (95.4%) cases, diarrhoea in 52 (48.1%) and vomiting in 38 (35.2%). Regular medication included aspirin in 39 (36.1%) of patients, NSAIDS in 19 (17.6%), and anti-coagulants in 12 (11.1%). Of the 108 admissions, 107 (99.1%) underwent lower GI endoscopy and 96 of these (89.7%) had biopsies taken for histology. One patient proceeded directly to surgical resection without prior endoscopic examination. Analysis of outcomes revealed rebleeding in 3 (2.8%) cases, with 5 (4.6%) patients requiring surgical resection; 30 day mortality was 3.7%. Readmission with IC was seen in 2 (1.9%) cases during the period studied. Conclusion: The incidence of IC appears to be rising, with the majority of patients being female and over 55 years of age. However, the surgery and mortality rates are lower than previously reported, and recurrence is rare. Disclosure of interest: None Declared. Reference: O'Neill S, Yalamarthi S. Systematic review of the management of ischaemic colitis. Colorectal Dis. 2012;14:e751–e763